The problem of activity in systemic scleroderma - N G Guseva; T A Nevskaya; Maya Nikolayevna Starovoitova (Современная ревматология, 2013)
The problem of systemic scleroderma (SSD) activity enters into the view of standardized patient examination and it is important for choosing a therapeutic complex, for determining the dose of drugs, and for monitoring therapy. Great difficulties in the determination of activity in SSD are caused by the pathogenetic and morphogenetic features of the disease. It should be emphasized that there are no clearly defined exacerbation and remission periods. It is difficult to differentiate the potentially reversible inflammatory changes determining the activity of SSD from the irreversible fibrous changes characterizing the severity of the disease. The laboratory parameters of inflammatory activity are also of little informative value. The complicated problem of activity in SSD is to be further investigated both to improve and modify existing indices and to search for a common specific marker and/or key pathogenetically and clinically relevant markers of disease activity.